Metabolic Imbalance Associated Mitophagy in Tumor Cells: Genesis and Implications (Journal of Cancer Research Updates, 2015)
Emerging knowledge supports the notion that metabolic reprogramming facilitates the progression of many cancers and in some it could be initiated by mutations in genes related to mitochondrial function. While dysfunctional mitochondria plays a pivotal role in driving metabolic reprogramming, mitophagy that recycles damaged mitochondria by selective and organized degradation appears to be vital for sustaining carcinogenesis. Although the potential of targeting mitophagy as a therapeutic strategy has still remained elusive, poor prognosis and therapeutic resistance of highly glycolytic tumors suggest that inhibitors of mitophagy could be potential adjuvant in radio- and chemotherapy of tumors. We briefly review the current status of knowledge on the interrelationship between mitophagy and metabolic reprogramming during carcinogenesis and examine mitophagy as a potential target for developing anticancer therapeutics and adjuvant.